El Concepto de Lo Público Aplicado a la Universidad - Neira-Barrera, H; Friz-Echeverria, C (Universidad de Chile, 2022)
The concept of public has been blurred. This is the framework within which some private universities pretend to be public, as well as the state owned ones, and that they must receive similar public subventions. The exegesis of the concept of public, based on the political arguments about religious liberty during the early years of Christianity and the contrast with some philosophical modern and contemporary texts wreck this pretention. It is possible to illuminate some aspects of the difference between what is public and what is private. This also illustrates that the exaltation of the blurred frontiers of the concept of public hides some normative pretentions on behalf of private universities market. © 2022 Universidad de Chile. All rights reserved.